Career or environmental crusade? –Irfan’s dilemma - Sulong, Farizah; Dent, Micheal; Mohd Alwi, Norhayati; Sulaiman, Maliah (Emerald Publishing, 2021)
The case is about Irfan, a Production Manager in Omicron, a small and medium-sized enterprise (SME) in Selangor, Malaysia, manufacturing automotive metal parts. Irfan is truly enthusiastic about environmental and cost-reduction tools and wishes to pursue it further. Irfan is facing the dilemma of how to align his passion for these tools with his future career choice. He is faced with three options – to remain in Omicron, to accept a job offer in another company or to establish his own consultancy firm. The case highlights the heavy involvement of Irfan in the implementation of a new environmental tool, Material Flow Cost Accounting (MFCA) in Omicron, and all the tasks, activities, benefits and challenges encountered., Irfan is excited about MFCA and wants to continue with it, due to the experience gained from its implementation, and its potential for future savings. However, he does not seem to observe a similar excitement among higher management. The case details an example of the implementation of MFCA for one of Omicron’s products and other relevant information that could serve as a guide to any future implementation either in Omicron, the new company or even his own company. The case also provides details about Omicron and how Irfan regard Omicron as his second family, a strong pull factor for Irfan to remain in Omicron.